#1

I don't want answers, I just need to know what to do.

For one equation it's:

(f o g)(2)

f(x) = 3x

g(x) = x+1

which makes it 3(x+1)

Do I take the two from (f o g)(2) here and substitute it for x or do I expand then substitute?

For one equation it's:

(f o g)(2)

f(x) = 3x

**2**__Bolded numbers are powers__g(x) = x+1

which makes it 3(x+1)

**2**Do I take the two from (f o g)(2) here and substitute it for x or do I expand then substitute?

#2

3((2)+1)

Right in hurr.

**2**Right in hurr.

#3

I don't want answers, I just need to know what to do.

For one equation it's:

(f o g)(2)

f(x) = 3x2Bolded numbers are powers

g(x) = x+1

which makes it 3(x+1)2

Do I take the two from (f o g)(2) here and substitute it for x or do I expand then substitute?

(f o g)(2) = f ( g(2) )

So take g(2) and then substitute that into f.

#4

Thanks, I have a couple answers though I don't know which is right, is it 12 or 27 or none of the above?

#5

g(x) = x + 1 => g(2) = 2 + 1 = 3

f(x) = 3 . x^2 => f( g(x) ) = 3 . ( g(x) )^2 = 3 . 3^2 = 3 . 9 = 27

f(x) = 3 . x^2 => f( g(x) ) = 3 . ( g(x) )^2 = 3 . 3^2 = 3 . 9 = 27

#6

g(x) = x + 1 => g(2) = 2 + 1 = 3

f(x) = 3 . x^2 => f( g(x) ) = 3 . ( g(x) )^2 = 3 . 3^2 = 3 . 9 = 27

Thanks a lot and thanks to toast too.